STATUS PEMANFAATAN IKAN CAKALANG (Katsuwonus pelamis) DI PERAIRAN KABUPATEN LUWU SULAWESI SELATAN - Muhammad Jamal Alwi; Hasrun Abdullah; Ernaningsih Aras (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2019)
Skipjack tuna (Katsuwonus pelamis), should be managed properly because even though it is renewable, natural resources can be depleted. One approach in managing fish resources is by modeling. The purpose of this study is to determine the maximum sustainable yield, the level of utilization and effort of skipjack tuna. Data on catches as well as catch efforts of skipjack tuna were collected from 9 fisheries year books of Luwu Kabupaten (District). The surplus production model used is the Schaefer, Fox, Walter & Hilborn model. Schaefer model obtained by MSY = 1541.08 tons and Fopt = 243 trips; Fox model obtained maximum sustainable yield value (YMSY) of 1602,244 tons, maximum sustainable fishing effort (fMSY) of 303 units and maximum sustainable CpUE value (UMSY) of 5.29 tons trip-1; the Walter & Hilborn model found potential stocks of sustainable reserves (Be) skipjack in Luwu district amounted to 935.72 tons year-1. Utilization rates of the skpjack tuina indicate the fish is still under exploitation.